Flexible Rechargeable Zinc-Air Batteries through Morphological Emulation of Human Hair Array - Fu, Jing (Advanced materials (Deerfield Beach, Fla.), 2016)
© 2016 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.